A Garden of Disorder: "Digital Unhu" from the Global South at the 2015 Venice Biennale. Issue 4 (2nd October 2018) - McClune, Caitlin
ABSTRACT: This article analyzes the 2015 Venice Biennale titled, All the World's Futures, an exhibition that consciously centralized nations outside of the West. In contrast to the desire to produce order in the previous Biennales of the modern era, All the World's Futures sought to express global conditions described as a complex network of financial, cultural, and political interdependence. Through discursive and textual analysis of the cultural artifacts, articles, and interviews of participating members of the 2015 Biennale, this article identifies the characteristics of 1) a growing awareness of the changing and variable dimensions of labor and capital, 2) a central concern with perspectives informed by historical legacies rooted in Africa, the African diaspora and the Middle East and, 3) a prominence placed on the affordances of digital technologies in collaborative production and distribution. These characteristics are examined within the context of gallery exhibitions, specifically, the Venice Biennale.